2016
DOI: 10.15294/komunitas.v8i2.5439
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Institution for Forest Conservation within a Changing Community: Insight from the Case of Upland South Sumatra

Abstract: Referring to the studies on the success of community forestry, the proponents suggest reducing the influence of the state to the people who maintain traditional institutions in forest management. However, knowledge about the interaction of formal and informal institutions in the context of changing smallholder farmers is still not fully understood. Through a phenomenological approach assessing the differences of forest conserving institutions'performance across villages in Semende, South Sumatra, it is analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…An interesting finding from this research is that even though the informal education that students get from the community and parents is in the form of storytelling and taboo culture, they do not see customs as things that must be obeyed solely so that disasters do not occur, such as understanding students outside Semende's social water literacy in Semende (Figures 2c and 2d). This is because these customs can be rationalized in the institution of meraje anak belai as part of fulfilling the needs of residents to irrigate fields inherited from their ancestors that cannot be traded [35,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding from this research is that even though the informal education that students get from the community and parents is in the form of storytelling and taboo culture, they do not see customs as things that must be obeyed solely so that disasters do not occur, such as understanding students outside Semende's social water literacy in Semende (Figures 2c and 2d). This is because these customs can be rationalized in the institution of meraje anak belai as part of fulfilling the needs of residents to irrigate fields inherited from their ancestors that cannot be traded [35,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Patorani culture is unique because its fishing process is carried out in the dry season using very traditional tools. The use of this traditional tool is closely related to the preservation Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktik dalam Bidang Pendidikan dan Ilmu Geografi 28(1), 2023, 52-63 of coral reefs, as their primary goal is to preserve the fish habitat (Martin, Suharjito, Darusman, Sunito, & Winarno, 2016). Coral reef preservation is accomplished by shielding them from the effect of modern, potentially damaging instruments.…”
Section: Form Of Patorani Local Knowledgementioning
confidence: 99%
“…Furthermore, others include pahomba, which is a prohibition on collecting forest resources surrounding the river flow, to maintain the existence of springs in NTT, subak in Bali, pill pasenggiri in Lampung, Maccera Tasi in North Sulawesi, Palia in Lore Lindu and Ibeiya in West Papua [36], [37] There has no yet been found any research that show indigenous water conservation in the community of Besemah-Semende's tribe. However Martin et al [38], [39] found that there is a close relationship between the existence of Tunggu Tubang's rice field and the preservation of ulu ayik forest wherein this forest contains a water source for irrigation of fields in Besemah-Semende's community.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on tunggu tubang in Semende [38]- [42], but there is no study on how water conservation is in this area. Guaranteeing the food availability of the extended family (apit jurai) necessitates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation